An analysis of workplace exposures to asbestos at three steel mills located in the United States (1972-1982). (November 2019) - Hollins, Dana; Burns, Amanda; Unice, Ken; Paustenbach, Dennis J
The objective is to present historical asbestos airborne concentrations associated with activities involving presumably asbestos-containing materials in steel mills. A total of 138 historical industrial hygiene air samples collected in three US steel mills from 1972 to 1982 were analyzed. The majority of samples were collected during relining of open hearth furnaces, stoves, and blast furnaces by steel mill bricklayers and bricklayer helpers. Over 75% of the samples ( n = 106) were collected for 50 min or less, four samples were collected for 227 to 306 min, and sample durations were not reported for the remaining 28 samples. Average airborne fiber concentrations measured during relining activities of open hearth furnaces, stoves, and blast furnaces were 0.21 f/cc, 0.72 f/cc and 0.13 f/cc phase-contrast microscopy (PCM), respectively. Measured airborne fiber concentrations of four time-weighted average (TWA) samples (>227 min) averaged 0.045 f/cc. Estimated 8-h TWAs concentrations averaged 0.34 f/cc for bricklayers and 0.2 f/cc bricklayer helpers. While 8-h TWA concentration estimates for monitored tasks/jobs may often have exceeded current Occupational Safety and Health Administration (OSHA) Permissible Exposure Limits (PELs), they did not exceed relevant contemporaneous occupational exposure standards. This analysis provides a better understanding of historical airborne asbestos exposures that bricklayers and other tradesmen experienced during furnace and stove work in the US steel mills.